2007
DOI: 10.1016/j.jtcvs.2007.02.041
|View full text |Cite
|
Sign up to set email alerts
|

Novel NOTCH1 mutations in patients with bicuspid aortic valve disease and thoracic aortic aneurysms

Abstract: This targeted analysis involving NOTCH1 exons previously implicated in familial and sporadic bicuspid aortic valve demonstrates overrepresentation of NOTCH1 missense variants among patients with bicuspid aortic valves and thoracic aortic aneurysms. Identification of aneurysm-predisposing susceptibility genes may lead to gene-directed surgical therapy of the ascending aorta for patients with bicuspid aortic valves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
174
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(180 citation statements)
references
References 24 publications
5
174
0
1
Order By: Relevance
“…Such an EMT defect is rescued by exogenous Fgf8, suggesting that Notch functions through Fgf8 to activate EMT of OFT cushions (High et al, 2009). NOTCH1 mutations are observed in some families with a multi-generation history of BAV and/or calcific aortic stenosis (Garg et al, 2005;Garg, 2006;McKellar et al, 2007;McBride et al, 2008;Rusanescu et al, 2008). Because Notch1 is capable of suppressing Runx2, which promotes calcification (Garg et al, 2005), NOTCH1 mutations in humans might cause RUNX2 upregulation with consequent valve calcification.…”
Section: Notch Signalingmentioning
confidence: 99%
“…Such an EMT defect is rescued by exogenous Fgf8, suggesting that Notch functions through Fgf8 to activate EMT of OFT cushions (High et al, 2009). NOTCH1 mutations are observed in some families with a multi-generation history of BAV and/or calcific aortic stenosis (Garg et al, 2005;Garg, 2006;McKellar et al, 2007;McBride et al, 2008;Rusanescu et al, 2008). Because Notch1 is capable of suppressing Runx2, which promotes calcification (Garg et al, 2005), NOTCH1 mutations in humans might cause RUNX2 upregulation with consequent valve calcification.…”
Section: Notch Signalingmentioning
confidence: 99%
“…It should be noted that NOTCH1 mutations can also cause an array of isolated cardiovascular defects, including aortic valve defects, hypoplastic left heart syndrome and tetralogy of Fallot (Garg et al, 2005;Kerstjens-Frederikse et al, 2016;McBride et al, 2008;McKellar et al, 2007;Mohamed et al, 2006). Such mutations include missense, nonsense and truncation mutations, implying that heterozygous loss of NOTCH1 function can lead to either AdamsOliver syndrome (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In a smaller unrelated family, a NOTCH1 frameshift mutation segregated with a similar aortic valve phenotype. Observations of missense NOTCH1 mutations in a subset (~5 %) of individuals with BAV have also been reported with supporting functional data indicating impaired Notch signaling [7,8]. These publications suggested that NOTCH1 haploinsufficiency was a cause of BAV in humans.…”
Section: Notch1 Mutations and Aortic Valve Diseasementioning
confidence: 62%